If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + 8t = 117 Combine like terms: 5t + 8t = 13t 13t = 117 Solving 13t = 117 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Divide each side by '13'. t = 9 Simplifying t = 9
| 8(3-x)-5=-3(3-2x) | | x/14=-27 | | 15-2h=6 | | 5.7q-2.5-5.3q=-0.6q-2.6 | | 4x-18=5+5 | | 5/4x-4/3y=-5/6 | | 2/3x+3/4y=1 | | 1/2x-y=-1/1 | | 5/2x/1/3y=1 | | 5.8q-4.4-5.3q=0.5q-4.1 | | 5.9q-4.4-5.3q=0.5q-4.1 | | 40x+10=2 | | 40x+5=2 | | Y=ln(x^2-4x)+4 | | -0.4x-0.4y=0 | | 40x+6=4 | | -x(-4)-7= | | 40x+6=3 | | -x(-7)-7= | | 40x+6=2 | | 0.5x-0.3y=0.3 | | h(t)=-16y^2+55+6 | | -x(0)-7= | | 6.7x/0.4y=11 | | h(t)=-4.9t^2+3 | | 12-28=6x+2 | | 9x-5y=750 | | 3b+4(b+6)=-4 | | 2x-1.5+6=3 | | 6x-16y=3 | | 2x-1.5+6= | | 2(2x+4)=x+2 |